Human stefin B: from its structure, folding, and aggregation to its function in health and disease - Žerovnik, Eva (Frontiers in Molecular Neuroscience, 2022)
Mutations in the gene for human stefin B (cystatin B) cause progressive myoclonus epilepsy of type 1 (EPM1), which qualifies as a neurodegenerative disorder. Dodecamer repeats in the promoter region of the gene is the most common change yet missense and frameshift mutations also appear. Human stefin B primarily acts as a cysteine cathepsins inhibitor but it also exhibits alternative functions. It plays a protective role against oxidative stress, likely via reducing mitochondrial damage and thus generating less mitochondrial reactive oxygen species (ROS). In accordance, lack of stefin B results in increased inflammation and NLRP3 inflammasome activation, producing more ROS. The protein is cytosolic but it also has an important role in the nucleus where it prevents cleavage of the N terminal part of histone 3 by inhibiting cathepsins L and B and thus regulates transcription and cell cycle. Furthermore, it has been shown that stefin B is oligomeric in cells and that it has a specific role in the physiology of the synapse and in vesicular transport. On the basis of our own data about stefin B structure, folding and aggregation we have proposed that it might regulate proteostasis, possessing a chaperone-like function. In this review paper I make a synthesis of these observations and derive some conclusions on possible sources of EPM1 pathology. Interacting partners of stefin B and other genes mutations leading to EPM1-like pathology are discussed and common pathways pinpointed.